Memahami Penyakit Paru Interstisial: Pengenalan Dini pada Layanan Kesehatan Primer - Latona Sidarta, Altama; Rasmin, Menaldi (PT Kalbe Farma Tbk., 2024)
Interstitial lung disease (ILD) encompasses a group of heterogeneous lung disorders with varying etiologies and clinical presentations. Early diagnosis is essential for timely intervention and improved patient outcomes. This mini-review highlights the significance of early diagnosis of ILD in primary health centers, focusing on the benefits and challenges associated with early detection, and the role of primary healthcare professionals in achieving a timely diagnosis. Primary healthcare professionals play a pivotal role in recognizing early signs and symptoms of ILD, conducting preliminary evaluations, and guiding patients through the diagnostic process. Collaborative efforts between primary healthcare professionals, pulmonologists, and radiologists are crucial to overcome these challenges and ensure timely diagnosis.